THE INFLUENCE OF FAMILY ENVIRONMENT, MOTIVATION, SELF-EFFICACY AND USE OF INSTAGRAM SOCIAL MEDIA ON ENTREPRENEURIAL INTERESTS OF STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS IN THE SPECIAL REGION OF YOGYAKARTA - Kurniawati, indah; Ayu Saputri, Yuke Dea (Kajian Ekonomi dan Bisnis, 2025)
This Study aims to determine the influence of family environment, motivation, self-efficacy, and the use of Instagram social media on the entrepreneurial interest of student. This research employs a quantitative method with primary data obtained from the distribution of 100 questionnaries using purposive sampling. The collected data were analyzed using multiple linear regression analysis. The result of the study found that self-efficacy does not have a significant positive effect on student entrepreneurial interest, meaning that the presence of confidence does not necessarily encourage interest in entrepreneurship. In contrast, the family environment, motivation, and the use of Instagram social media have a significant positive effect on entrepreneurial interest.